Relationships between the jumping and sprinting kinetics of elite, collegiate football athletes - Boone, J.; Mangine, G.; Van Dusseldorp, T.; Feito, Y.; McDougle, J.; Stratton, M.; Velazquez, N. (The Journal of Strength and Conditioning Research, 2021)
Speed and power are thought to be important in football athletes and these traits are indirectly assessed through a variety of field tests. Sprinting time over 10-40 yards is used as a speed metric, while standing broad jump (SBJ) distance and vertical jump (VJ) height are indicative of power. However, the resultant test scores (i.e., time, height, or distance) do not adequately describe the kinetics occurring throughout each movement, which may have greater importance to on-field success. Further, it is not clear whether kinetics during each movement are related. Strong relationships would eliminate the need to perform each assessment. Purpose: To evaluate the relationships between jumping and sprinting kinetics in elite, collegiate football athletes. Methods: Over a three-year period, 72 collegiate football athletes (22.4 ± 0.9 years, 187.0 ± 7.0 cm, 112.8 ± 23.2 kg) volunteered to complete baseline assessments of 10-yard sprinting, SBJ, and VJ, prior to initiating a preparatory training program for their respective professional football combine or pro-day. Following a standardized warm-up, each athlete completed 1-3 maximal efforts in each performance test. To measure kinetics, athletes were tethered via a waist belt to a robotic, cable-resistance device for the 10-yard sprint and SBJ, and to a linear position transducer during VJ. Peak rate of force development (RFDPeak), total work, and average force (FAVG), velocity (VAVG), and power (PAVG) were quantified during the first (STP1) and second (STP2) steps of the 10-yard sprint, while their slope was calculated across remaining steps (STPR). Peak and average values for each kinetic measure were also calculated during SBJ and VJ. To account for the influence of cord angle on resultant kinetics, partial correlations controlling for height were calculated between all sprinting and jumping variables. Results: FAVG was the only kinetic measure from STP1 related to jumping performance (SBJ RFDPeak: r = -0.24, p = 0.046). From STP2, total work was positively related to SBJ PAVG (r = 25, p = 0.039) and negatively related to average VJ force and power (r = -0.26 to -0.34, p < 0.05). Further, VJ FAVG and PAVG were negatively associated (p < 0.05) with several kinetic measures during STP2 (r = -0.25 to -0.38). Positive relationships were seen for FAVG during both STPR and VJ (r = 0.26, p = 0032), as well as between VAVG from STPR and SBJ VPeak (r = 0.39, p = 0.001), PPeak (r = 0.35, p = 0.003), and RFDPeak (r = 0.28, p = 0.018). The only negative relationship observed in relation to STPR was between its RFDPeak and SBJ PPeak (r = -0.24, p = 0.046). No other significant relationships were observed. Conclusions: The data suggests that relationships exist between standing broad jump and sprinting kinetics, but they are weak. In contrast, vertical jump kinetics only appear to be related to sprinting kinetics in a limited capacity, with higher vertical jump kinetics being associated with reduced second step sprinting kinetics. Practical Applications: Force, velocity, and power are uniquely expressed during jumping and sprinting, and enhanced performance in one movement may not translate to the other. Since short-distance sprinting, standing broad jump, and vertical jump are all thought to be important in football, athletes and coaches should continue to train for and test each of these specific movements.